Synthesis and characterization of Cu2Zn1-XCdxSnS4 quinternary alloy structure nanostructures using sol-gel electrospining technique - Ibraheam, Authman Salim (Institute of Nano Electronic Engineering, 2016)
The objective is as the followings to study of various Cd concentration on the structural, morphological, optical and electrical properties of the Cu2Zn1-xCdxSnS4 quinternary alloy nanostructures using spin coating and electrospinning technique grew on glass substrate; to research the of copper (Cu) concentration on the structural, morphological and optical properties of Cu2Zn0.8Cd0.2SnS4 quinternary alloy nanostructures grew on glass substrate; to elaborate the effect of etching times porous silicon (PS) as substrate prepared by electrochemical etching method followed by deposited Cu2Zn1-xCdxSnS4 for characterization, analysis, optical properties and electrical properties of current-voltage (I-V) characteristics and UV photoresponse of the Ag/n-PS /Cu2Zn1-xCdxSnS4/Ag heterojunction when x= 0, 0.6, 1; to investigate the effect of various Cd concentretion on the structural, morphological and optical properties of Cu2Zn1-xCdxSnS4 quinternary alloy nanostructures using spin coating technique prepared on oxidized silicon (SiO2) substrate and their application in the detection of DNA sequence from Dengue type-2; to study the effect of various Cd concentration on the structural, morphological, optical and electrical properties of the Cu2Zn1-xCdxSnS4 quinternary alloy nanostructures using spin coating technique grew on GaN substrate .